A Re-Examination of Measures for Typifying Political Parties’ Philosophies, Policies and Democracy in Free Societies and Lessons for sub-Saharan Africa’s Emerging Societies - MASUMBE, Peter SAKWE (Advances in Social Sciences Research Journal, 2021)
This article re-examines measures on how plentiful political parties’ philosophies and policies implant democracy in free societies, to adduce lessons for political parties in sub-Saharan Africa’s emerging societies. From Bawn et al.’s (2012) charaterising framework on political parties’ in free societies, I expand their theory of political parties by affirming that, interest groups, activists and lay voters, rather than leaders of political parties must be the key actors in policy-making and democratisation; as groups’ alliances develop collective plans and screen contestants for party nominations based on loyalties to parties’ agendas. This premise contrasts with those theories, which believe that, parties are tools for self-seeking leaders. The variance edifies, because parties dominated by interest groups, activists and voters, rather than leaders, are more responsive to voters’ preferences. Thus, I debunk the prevailing practices of political parties’ philosophies and policies in sub-Saharan African societies, wherein elective offices aspirants rebuff popularising in solving social problems, but scheme on narrow self-seeking predatory ambitions at the electorates’ chagrin.